2022
DOI: 10.3390/curroncol29030110
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Study to Evaluate the Associations of Nodal Stage, Lymph Node Ratio and Log Odds of Positive Lymph Nodes with Survival in Patients with Small Bowel Adenocarcinoma

Abstract: Purpose: This study aimed to determine the real-world prognostic significance of lymph node ratio (LNR) and log odds of positive lymph nodes (LOPLN) in patients with non-metastatic small bowel adenocarcinoma. Methods: Patients diagnosed with early-stage small bowel adenocarcinoma between January 2007 and December 2018 from a large Canadian province were identified. We calculated the LNR by dividing positive over total lymph nodes examined and the LOPLN as log ([positive lymph nodes + 0.5]/[negative lymph nodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In a retrospective analysis of 2772 SBA patients registered in the SEER database between 1988 and 2010, survival decreased as the N ratio increased, and the poorest median survival (16 months) was that of a group with N ratio > 0.4 [ 13 ]. Another study published in 2022 year was used an N ratio cutoff of 0.4, and found that the N ratio, the number of lymph nodes resected, and the number of positive lymph nodes enhanced prognostic accuracy [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective analysis of 2772 SBA patients registered in the SEER database between 1988 and 2010, survival decreased as the N ratio increased, and the poorest median survival (16 months) was that of a group with N ratio > 0.4 [ 13 ]. Another study published in 2022 year was used an N ratio cutoff of 0.4, and found that the N ratio, the number of lymph nodes resected, and the number of positive lymph nodes enhanced prognostic accuracy [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are over 40 different subtypes of small bowel cancer, with the three most common being neuroendocrine tumors, adenocarcinomas, and mesenchymal tumors [3] . Lymph node metastasis is an independent risk factor for recurrent postoperative metastasis in small bowel cancer patients [4] . Accurate staging, particularly in assessing the presence or absence of lymph node metastasis, is crucial for selecting treatment options and determining the prognosis for small bowel cancer patients.…”
Section: Introductionmentioning
confidence: 99%